Cytotoxic Antibody Detection by Means of Flow-Cytometric Cross-Match - ATA, PINAR (ELSEVIER SCIENCE INC, 2017)
Background. Complement-dependent lymphocytotoxicity (CDC-XM) and flowcytometric (FCXM) cross-match are analyzed individually for each donor and recipient pair, because these techniques have fundamental differences for the evaluation of histocompatibility. Lately, cytotoxic flow-cytometric cross-match (cFCXM) has been developed as an alternative to both CDC-XM and FCXM techniques. We evaluated the limits of cFCXM with the use of different positive serum dilutions. Methods. CDC-XM, FCXM, and cFCXM tests were performed with the use of commercially available negative and positive serum samples and lymphocytes from healthy donors. Results. Complement-dependent cell death was successfully detected with the use of cFCXM. Complement-dependent cell death ratios in cFCXM were similar those in CDCXM. With cFCXM, not only complement-dependent cell death but also IgG binding could be detected within a single assay. At higher concentrations of the positive serum, IgG-fluorescein isothiocyanate (FITC) mean fluorescent intensity (MFI) values detected with the use of cFCXM were less than those of conventional FCXM. Correspondingly, for dead cells, MFI values of IgG-FITC were less than those of live cells in higher positive serum concentrations in the cFCXM assay. Moreover, our results demonstrated that in cFCXM analysis, the decreasing ratio of dead cells at increasing positive serum dilutions was not in parallel with the same decrease in IgG-FITC MFI values. Conclusions. The cFCXM technique detects complement-mediated cytotoxic cell death with the additional ability to show IgG binding in the same tube and therefore may reduce the necessary bench time and workload.
Keywords: RENAL-TRANSPLANTATION; BINDING; ASSAY; IGG